2008
DOI: 10.1111/j.1937-8327.2004.tb00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Culture and Socio-cultural Values: Perceptions of Managers and Employees in Five Economies in Transition

Abstract: This survey-based study compared socio-cultural values and perceptions of organizational culture characteristics held by more than 3,300 managers and employees in twelve business organizations in Hungary, Russia, Georgia, Kazakhstan, and the Kyrgyz Republic. Significant differences were found between the five countries on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The study of CSR practices in Kazakhstan bears significant importance for both business communities and policymakers. Managers in this transition economy are still confused of constitutes of ethical business behaviour and acceptable CSR practices (Altaliyeva, 2003;Puffer and McCarthy, 2003;Cseh et al, 2004;Chapple and Moon, 2007;Preuss and Barkemeyer, 2011). Cultural influences from the past Soviet regime and the recent influence of the Anglo-Saxon lifestyle have made it difficult to hypothesize well acceptable ethical standards for Kazakhstan society (Cseh et al, 2004;Matten and Moon, 2008).…”
Section: Csr In Kazakhstan: Profile Of An Emerging Market and Researcmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of CSR practices in Kazakhstan bears significant importance for both business communities and policymakers. Managers in this transition economy are still confused of constitutes of ethical business behaviour and acceptable CSR practices (Altaliyeva, 2003;Puffer and McCarthy, 2003;Cseh et al, 2004;Chapple and Moon, 2007;Preuss and Barkemeyer, 2011). Cultural influences from the past Soviet regime and the recent influence of the Anglo-Saxon lifestyle have made it difficult to hypothesize well acceptable ethical standards for Kazakhstan society (Cseh et al, 2004;Matten and Moon, 2008).…”
Section: Csr In Kazakhstan: Profile Of An Emerging Market and Researcmentioning
confidence: 99%
“…Managers in this transition economy are still confused of constitutes of ethical business behaviour and acceptable CSR practices (Altaliyeva, 2003;Puffer and McCarthy, 2003;Cseh et al, 2004;Chapple and Moon, 2007;Preuss and Barkemeyer, 2011). Cultural influences from the past Soviet regime and the recent influence of the Anglo-Saxon lifestyle have made it difficult to hypothesize well acceptable ethical standards for Kazakhstan society (Cseh et al, 2004;Matten and Moon, 2008). However, adoption of high ethical standards and extending CSR activities beyond immediate business benefit is necessary for gaining credibility in the business world (Puffer and McCarthy, 2003;Chapple and Moon, 2007;.…”
Section: Csr In Kazakhstan: Profile Of An Emerging Market and Researcmentioning
confidence: 99%
“…They conducted a survey of work settings in seven countries and concluded that when the data were compared on a site-by-site basis (as compared to an overall country view), differences were observed that could not be accounted for using national culture alone. Cseh, Ardichvili, Gasparishvili, Krisztián, and Nemeskéri (2004) conducted a study comparing sociocultural values and perceptions of organizational culture among over 3,000 employees in five countries and provided data suggesting that organizations develop a specific culture under the influence of both national cultures and contextual settings that include economic, social, and political conditions. In the context of design and the delivery of performance interventions within organizations, Hatala and Gumm (2006) identified five contextual factors that practitioners should consider-economic (e.g., budget, extent of financial rewards), social (e.g., influential leaders within an organization), communication (e.g., how it is viewed and used), leadership (e.g., how leaders are selected and developed), and political (e.g., what is deemed acceptable in the organization).…”
Section: Organizational Culture and Hptmentioning
confidence: 99%
“…However, organizational culture is also infl uenced by broader processes taking place in society. On the one hand, the role of national culture has been stressed (e.g., Hofstede et al 1990 ;Cseh et al 2004 ;Koopman et al 1999 ;Mead 1994 ;Van Muijen et al 1999 ) , but on the other hand, the impact of industry ideologies which facilitate certain organizational values in the organization should be considered as important external environmental determinants of organizational culture (see Gordon 1991 ;Padaki 2000 ; ) . Besides, several organizational characteristics (organization's size and age) can be seen as factors that mediate the infl uence of internal and external factors of organizational culture (see Vadi and Alas 2006 ) .…”
Section: Organizational Culturementioning
confidence: 99%